The end of the oppressive empire is at hand: The thrust of the oracles in Jeremiah 50–51 Masoretic text - Marius D. Terblanche (Verbum et Ecclesia)
The article seeks to bring the effect of the encounter with the Neo-Babylonian Empire on the oracles in Jeremiah 50–51 Masoretic text (MT) to the fore. In these oracles, the Babylonian imperial claim of global rule from Babylon as a manifestation of the kingship of Marduk is countered with the counter-imperial claim that Yahweh is king. Babylon was merely a golden cup in the hand of Yahweh. The city of Babylon, which was built by Marduk, would suffer a fate similar to that of Jerusalem. It is argued that Empire Studies offer fresh insights into the apparent tension between the Oracles against Babylon and the pro-Babylonian sections of the book of Jeremiah. The contrast between them lies primarily in the manner in which the Babylonian imperial claims are dealt with. While the pro-Babylonian sections of the book of Jeremiah present a disguised transcript of resistance, the oracles against Babylon openly confront the Babylonian imperial claims. Utilising insights provided by Empire Studies, the article scrutinises the effect of the encounter with the Neo-Babylonian Empire on the oracles in Jeremiah 50–51 MT. Finally, the contrasting ways in which the oracles against Babylon and the oracle in Jeremiah 27:5–11, which is seemingly the most pro-Babylonian part of the book of Jeremiah, confront the imperial claims of Babylon, are considered.